Answer:
Explanation:
Here y = -x^2 + 36.
We can choose x values pretty much at random and then calculate the associated y values:
x y = -x^2 + 36
---- --------------------
0 36
2 -2^2 + 36 = 32
-2 -4 + 36 = 32
3 -9 + 36 = 27
You did not share the equation of the slanted line. Let's assume that the equation of this line is y = mx + b. The first two points in the table above are (0, 36) and (2, 32). We could find the equation of this line as follows:
Slope: as we move from (0, 36) to (2, 32), x increases by 2 and y decreases by 4. Thus, the slope is m = rise / run = -4/2, or -2. Using info from the point (0, 36), we find the y-intercept of this straight line:
y = mx + b becomes 36 = m(0) + b, so b = 36, and the line is y = -2x + 36.
We need to find the points of intersection of y = -2x + 36 and y = -x^2 + 36. We can equate these equations to eliminate y: -2x + 36 = -x^2 + 36, or
-2x = -x^2. Equivalently, 2x - x^2 = 0, or (x)(2 - x) = 0. Then x = 0 and x = 2.
This says that the line and the parabola intersect in at least two places:
(0, 36) and (2, 32).